COMPARISON OF THE COOPERATIVE LEARNING MODEL TYPE TGT AND NHT TO STUDENTS' COGNITIVE ABILITIES - Ismana, Larasati Nindya; Wibowo, Yuni (Universitas Negeri Yogyakarta, 2025)
This study aims to determine the differences in students' cognitive learning outcomes after applying the Team Game Tournament (TGT) and Number Head Together (NHT) cooperative learning models to the subject of coordination systems for class XI at SMA Negeri 1 Karangmojo. This quasi-experimental study used a pre-test-post-test non-equivalent control group design. Sampling was carried out using a purposive sampling technique. Data collection used pre-test and post-test questions in the form of multiple-choice exam questions. The instruments used in this study were validated modules, pre-test questions, and post-test questions, which were validated for content and construct by experts. The data analysis techniques employed were the Wilcoxon test and the Mann-Whitney U test, both using SPSS version 26.0, to compare effect size values. This study shows the following results: (1) There is an increase in students' cognitive abilities after the use of cooperative learning models, both TGT and NHT types. (2) There are differences in the results of increasing students' cognitive abilities after the application of cooperative learning models of TGT and NHT types. (3) The cooperative learning models of the TGT and NHT types based on the Effect Size value have a high influence on increasing students' cognitive abilities with a Cohen's NHT value of 2.838, which is greater than the Cohen's TGT value of 1.025. The results of this study are expected to be used by teachers as a basis for selecting a learning model, especially in biology education.